Migrant nurses can help solve Kiwi nursing shortage - Hernandez M (NZME Educational Media - Health Central, 2018)
Monina Hernandez, the president of the Filipino Nurses Association of New Zealand, argues that granting longer migrant nurse visas to internationally qualified nurses can help solve the nursing shortage.
Keywords: migrant nurses, Filipino nurses, New Zealand nursing shortage